2022
DOI: 10.1155/2022/4061043
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Learning Model-Based Assessment of Enteral Nutrition Support in Neurosurgical Intensive Care Patients

Abstract: To observe the clinical efficacy of early enteral nutrition application in critically ill neurosurgical patients, in this paper, we have developed a prediction model for enteral nutrition support in neurosurgical intensive care patients which is primarily based on an integrated learning algorithm. Additionally, we have compared the prediction performance of each model. The patients were divided into control and combined treatment groups according to the random number table method, and 175 patients in each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a recent study, involving neurosurgical patients, 350 patients were randomized to receive enteral feeding only or parenteral nutrition and low-energy enteral feeding administered progressively. A prediction model of enteral nutrition support for severe neurosurgical patients was established based on an integrated learning algorithm, and the prediction performance of each model was compared [34]. Our group used a supervised machine learning approach to examine EFI along the early acute phase as a predictor of clinical outcomes (including ICU mortality, hospital mortality, 28-day mortality, 90-day mortality and length of stay greater than 7 days) in critically ill patients [35].…”
Section: Predicting Outcomes Using Machine Learning In Enteral Feedingmentioning
confidence: 99%
“…In a recent study, involving neurosurgical patients, 350 patients were randomized to receive enteral feeding only or parenteral nutrition and low-energy enteral feeding administered progressively. A prediction model of enteral nutrition support for severe neurosurgical patients was established based on an integrated learning algorithm, and the prediction performance of each model was compared [34]. Our group used a supervised machine learning approach to examine EFI along the early acute phase as a predictor of clinical outcomes (including ICU mortality, hospital mortality, 28-day mortality, 90-day mortality and length of stay greater than 7 days) in critically ill patients [35].…”
Section: Predicting Outcomes Using Machine Learning In Enteral Feedingmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%